Ageing and learning: What do they mean to elders themselves?. Issue 2 (3rd May 2016) - Tam, Maureen; Chui, Ernest
ABSTRACT: This paper is about a quantitative study which has examined and elucidated the conceptualizations of ageing and learning by a group of elders in Hong Kong. In more specific terms, the study has investigated how this group of older people understood the meaning of successful ageing and elder learning in the context of their later lives. Based on the 'Learning and Ageing Survey 2013' with a sample of 519 older adults in Hong Kong, the study aimed, first, to describe and conceptualize the meaning of ageing and learning as elders experienced it in later life; second, to investigate why and how elders engaged or did not engage, in organized learning, by comparing the differences between the 'learning' and 'non-learning' groups in terms of their personal characteristics, conceptualizations of learning, and the barriers to participation; third, to identify important learning issues for older learners, including their interests, needs, motivations, and learning preferences; and finally, to investigate the relationship between learning and successful ageing, and between learning and the overall well-being and satisfaction of elders in their later lives. The research findings and outcomes of the study provide insights into the experience and views of elders concerning ageing and learning, which contribute to the global understanding and knowledge base for elder learning and successful ageing; and which serve to inform the development of policy and practice geared to the planning and provision of programmes for learning in older age.